The Effectiveness of Hypnotherapy Movement and Affirmation (HYMA) on Anxiety Status with A Review of Changes in Blood Profiles and Cortisol Hormone Levels in Schizophrenia Patients - Ade Sucipto; Sri Rahayu; Iqlila Romaidha; Nurul Maulidatul Khabsy (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia is a condition characterized by abnormal social behavior and an inability to understand reality. Mental health Schizophrenia is a severe and serious mental disorder that can become chronic from a young age because it involves changes in physical, psychological and socio-cultural aspects. Inappropriate treatment of schizophrenia patients will always have an impact on anxiety conditions, slurred or confused thinking, decreased auditory hallucinations, reduced social involvement and emotional expression, and lack of motivation. Management is carried out with pharmacological and non-pharmacological complementary, one of which is Hypnotherapy Movement And Affirmation. Objective: The study aims to analyze the effect of Hypnotherapy Movement And Affirmation (HYMA) On Anxiety Status With A Review Of Blood Profile Changes and Cortisol Hormone In Schizophrenia Patients. Method: The research design used quasi-experimental with a pretest - posttest approach with control group design. The research population was Schizophrenia patients with purposive sampling. The sample in this study was 18 respondents, divided into an experimental group of 9 respondents and a control group of 9 respondents. The experimental group was given Hypnotherapy Movement and Affirmation with the implementation of the action carried out for 2 weeks and each session was carried out for 20 minutes, while the control group only received basic treatment from the Health Center. Result: Based on the Mann Whitney test of the experimental group of cortisol measurements obtained significant results of 0.017 (p <0.05), Erythrocyte measurements obtained significant results of 0.507 (p> 0.05), and Leukocyte measurements 0.930 (p> 0.05). It can be concluded that there is a significant difference in the Complementary Hypnotherapy Movement And Affirmation (HYMA) combination group on cortisol hormone measurements, while there is no significant difference in the measurements of erythrocytes and Leukocytes of respondents. Conclusions: Combination of Hypnotherapy Movement And Affirmation (HYMA) therapy is able to reduce anxiety scale and cortisol hormone levels. Although the profile of Erythrocyte and Leukocyte values has not shown significant changes and associations with schizophrenia in the experimental group or the control group.